Transitory Spontaneous Remission of Myelodysplasia in an Elderly Man while Receiving Intravesical Bacillus Calmette-Guérin for Bladder Cancer: A Case Report and Review of the Literature - Murray, Nigel P.; Fuentealba, Cynthia; Salazar, Isidora; Salazar, Aníbal; Lopez, Marco Antonio; Minzer, Simona (Case Reports in Hematology, 2018)
Myelodysplasia is a clonal disorder characterized by progressive cytopenias. Intravescial BCG is standard immunotherapy for superficial bladder cancer. We present a patient with transfusion-dependent myelodysplasia whose blood counts normalized during treatment with intravesical BCG for bladder cancer. After finishing treatment, the patient became transfusion dependent once more. We discuss possible mechanisms to explain this case report.